Forms Of Manifestation Of Intellectual Potential In The Context Of Labor Relations (Czech Journal of Multidisciplinary Innovations, 2025)
The article analyzes the issues of scientific study of the activities of existing social institutions in society in the development of the human factor and the implementation of intellectual potential of these institutions, their systematic analysis. Also, special attention is paid to the issues of scientific forecasting of trends in the process of intellectual development and the formation of public opinion in the social situation. Assessing and predicting the impact and possibilities of intellectual potential in society on the process of organizing a decent lifestyle by young people requires a systematic analysis and determination of the state of existing institutions in society